Injectable Tannin-Containing Hydroxypropyl Chitin Hydrogel as Novel Bioactive Pulp Capping Material Accelerates Repair of Inflamed Dental Pulp - Linfang Zhou; Wenjie Shi; Xinye Zhang; Ming Liu; Lu Zhang; Xulin Jiang; Zhi Chen (Biomolecules)
Conventional pulp capping materials have limited anti-inflammatory capacity. It is necessary to develop more effective pulp capping material for the treatment of inflamed pulps. Tannic acid (TA) is a natural, water-soluble polyphenol with antimicrobial and anti-inflammatory properties. This study aimed to investigate the effects of a tannin-containing hydroxypropyl chitin hydrogel (HPCH/TA hydrogel) as an innovative pulp capping material. The physicochemical properties of the composite hydrogels were characterized. The effects of HPCH/TA hydrogel as a pulp capping material were evaluated in vitro and in vivo. The underlying mechanism of the anti-inflammatory effects of HPCH/TA hydrogel was explored. The HPCH/TA hydrogel demonstrated favorable temperature sensitivity, injectability, and antibacterial properties. In vitro, the HPCH/TA hydrogel effectively promoted the proliferation of human dental pulp cells and inhibited interleukin-1β, interleukin-6, and tumor necrosis factor-α expression, possibly by suppressing the nuclear factor kappa-B pathway. In vivo, on the fourth day after capping, the HPCH/TA hydrogel group showed lower inflammatory scores compared to the control and iRoot BP Plus (commercial pulp capping material) group. By the sixth week, complete reparative dentin formation was observed in the HPCH/TA hydrogel group, with no difference in thickness compared to the iRoot BP Plus group. Collectively, the HPCH/TA hydrogel holds promise as a bioactive pulp capping material for promoting the repair of inflamed pulp in vital pulp therapy.